Testing the superstar firm hypothesis - Alexander Schiersch; Caroline Stiel (Journal of Applied Economics, 2022)
Firms with superior productivity, labeled superstar firms, are argued to be the link between rising concentration and the fall of the aggregate labor share in the US. This analysis confirms that similar evidence is found within the European context: the market share and firm size increase, whereas the labor share decreases with productivity. One of the much discussed mechanisms behind this development is the spreading of fixed overhead labor costs: Highly productive firms gain market share, and can simultaneously spread fixed overhead labor costs over more output, thereby reducing their own labor share and the aggregated labor share of the industry. We show that this mechanism can be tested empirically. However, using German firm-level data, we do not find any empirical evidence of it. Our analysis contributes to the ongoing debate by removing one of the proposed mechanisms from the list of potential explanations for the rise of superstar firms.
Keywords: 330; total factor productivity; firm size; labor share; Superstar firms